Letter - Winstanley, E.
029-0055-001 Telegraphic address: "Wholesale Manchester" Telephone: Blackfriars 1212 Extension No. Please address your reply: Co-operative Wholesale Society Limited, Exporters, Buying and Shipping Agents, 1, Balloon Street, Manchester, 4. Cable Codes: A.B.C., 6th and 7th editions; Western Union 5 letter; Bentley Complete Phrase; Bentley Second Phrase; A.1. MARCONI, and Private. Our reference EXPORT ST/HP. 345 Your reference 5th January, 1938. The Trades Union Congress General Council, Transport House, Smith Square, London Dear Sirs, We confirm the message transmitted to you today through the medium of our London Branch informing you that the s.s. LUCKY will sail from Hull to Barcelona at weekend, and that the charterers, the Spanish Government, are prepared to permit us to place on board, 80 tons Sugar. Since receiving this information we have been in communication with the loading brokers at Hull who unfortunately advise us that all the available space in the steamer has in the meantime been booked and consequently they are unable to accent any cargo from us whatsoever. However, we have been able to arrange by s.s. MADGE LLEWELLYN closing in Liverpool at weekend also for Barcelona to take the 1 ton of Ships Biscuits as ordered by you on the 24th December, and will advise you of further developments as early as possible. At the present date, we understand the insurance premium on shipments to Spanish Government ports is £10.10. 0.%, but this rate will be subject to confirmation. Providing the rate does not materially increase we will effect a cover as in the case of past consignments. Yours faithfully, E. Winstanley Export Department. 292/946/29/55